Biological maturity and the anthropometric, physical and technical assessment of talent identified U16 Australian footballers - Cripps, A. J.; Joyce, C.; Woods, C. T.; Hopper, L. S. (International Journal of Sports Science & Coaching, 2017)
This study compared biological maturation, anthropometric, physical and technical skill measures between talent and non-talent identified junior Australian footballers. Players were recruited from the under 16 Western Australian Football League and classified as talent (state representation; n = 25, 15.7 ± 0.3 y) or non-talent identified (non-state representation; n = 25, 15.6 ± 0.4 y). Players completed a battery of anthropometric, physical and technical skill assessments. Maturity was estimated using years from peak height velocity calculations. Binary logistic regression was used to identify the variables demonstrating the strongest association with the main effect of 'status'. A receiver operating characteristic curve was used to assess the level of discrimination provided by the strongest model. Talent identified under 16 players were biologically older, had greater stationary and dynamic leaps and superior handball skill when compared to their nontalent identified counterparts. The strongest model of status included standing height, non-dominant dynamic vertical jump and handball outcomes (AUC = 83.4%, CI = 72.1%-95.1%). Biological maturation influences anthropometric and physical capacities that are advantageous for performance in Australian football; talent identification methods should factor biological maturation as a confound in the search for junior players who are most likely to succeed in senior competition. ABSTRACT FROM AUTHOR